Megachile (Megachile) montivaga (Hymenoptera: Megachilidae) nesting in live thistle (Asteraceae: Cirsium) - Orr, Michael C.; Portman, Zachary M.; Griswold, Terry L. (Journal of Melittology, 2015)
Although Megachile Latreille (leafcutter bees) are well known for their diverse nesting habits, records of the genus nesting in live plants are rare. Here, we report the widespread Megachile (Megachile) montivaga Cresson nesting in live thistle (Cirsium neomexicanum Gray), the first explicit record of this behavior in the Nearctic.